STATE OF THE ENVIRONMENT IN THE NIGER DELTA AREA OF ONDO STATE - F.A. Olorunlana (European Scientific Journal, ESJ, 2013)
The geomorphological agents at work in the coastal zone are winds, the astronomicallygenerated tides, the wind-generated waves, and various forms of current flow. These generate specific geomorphic processes and interact to produce an energy input which shapes and modifies the coast. Through feedback mechanisms, the developing morphology influences geomorphological processes, thereby becoming a factor influencing subsequent coastal evolution. Man, through his activities, is also a variable in this geomorphological equation. Within the last three decades, accelerated coastal erosion, sea incursion and flooding have surfaced and reached alarming dimensions in some other parts of the niger Delta, notably along the transgressive mud coast in Ondo state. This paper examines the state of the environment in the Western Niger Delta area of Ondo State. It identifies the environmental problems in the area and also at the environmental and socio-economic impacts of these problems. Possible and practicable recommendations were proffered in an attempt to reduce or check the trend and scenario of these problems in the area.